Correlação da expressão gênica de TBET, GATA3 E FOXP3 com o desenvolvimento de mielopatia em pacientes portadores do HTLV-1 - OLIVEIRA, Allef William França de (2023)
Human T-cell lymphotropic virus type 1 (HTLV-1) is an endemic virus in our region. It is associated with the development of several disabling diseases and symptoms, such as HTLV 1 Associated Myelopathy (HAM/ TSP). The gene expression of the transcription factors TBET, GATA3 and FOXP3, in the development of this myelopathy, seems to be determinant to the course of the disease. This observational, analytical and cross-sectional study aimed to quantify the gene expression of these transcription factors in the steps of myelopathy manifestation, in patients with HTLV-1. Patients older than eighteen years old, diagnosed with HTLV-1, attended and followed up at the Laboratory of Clinical and Epidemiology of Endemic Diseases of the UFPA Tropical Medicine Center, participated in this study. Clinical data and blood samples were collected from patients for further isolation and quantification of RNA for cDNA synthesis and then quantification of the gene expression of β-Actin, GAPDH, TBET, GATA3 and FOXP3. The results showed 76 patients, 39.47% with HAM/ TSP, 35.53% Asymptomatic and 25% were Monosymptomatic/Oligosymptomatic patients (MOS). In the correlation of transcription factors with clinical forms, there was a higher expression of TBET in patients with HAM/ TSP, without statistical significance (p = 0.4282); the GATA3 and FOXP3 factors were expressed more in the asymptomatic ones, with predominance of GATA3 (p = 0.0007). GATA3, when related to FOXP3, showed a significant predominance in asymptomatic individuals (p = 0.0019) and MOS (p = 0.0209). It is concluded that the GATA3 factor seems to be determinant to a different clinical course in the evolution of myelopathy (incomplete form).